Mindfulness As a Meta-Predictor of Personal and Professional Competence of a Labor Subject - Semenov, D (KnE Life Sciences, 2018)
Background: The article deals with psychological factors affecting professional development of a labor subject under the conditions of socio-economic shocks, information overloads and modernization of virtually all areas of professional activities. The research looks at psychological predictors of an individual’s constructive professional development, as well as conditions for building coping skills in such critical situations as stress, conflict, frustration, etc., which are the causes of emotional burnout, professional destruction, deviant behavior, deterioration of occupational and psychological health, psychosomatic disorders, and so on. The analyzed phenomenon is a labor subject’s ”psychological immunity” to professional destruction stemming from multiple increase in intensity of negative impact on individual psycho-emotional state. The research defines the role of psychological immunity in constructive professional development and personal and professional competence. Design: Academic novelty of the article consists in analysis of the psychological construct of mindfulness, which is new to Russian science. The author views this construct as a psychological meta-predictor of personal and professional competence belonging to the structure of personal and cognitive features of individuals and ensuring effective unleashing of their personal potential. Results: The research has found out the link between the psychological predictors of constructive professional development and the mindfulness level of an individual, which makes it possible to broaden the understanding of individual psychological characteristics and capabilities of labor subjects in their topmost achievements, to define strategies for effective use of psychological and intellectual resources of a professional, for choice between destructive and constructive professional development in favor of the latter and for shaping personal and professional competence. Conclusions: On the meta-cognitive level mindfulness contributes to building a labor subject’s psychological immunity for overcoming professional destruction, determines acquisition of personal and professional competences required for constructive professional development and an increase of personal and professional competence. Keywords: Mindfulness, psychological predictors, meta-concept, personal and professional competence.